Does immigration help alleviate economy-wide labour shortages? - Pierre Fortin (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2024)
I study the impact of Canada's expansive immigration policy launched in 2016 on labour shortages in six regions of the country, particularly in Quebec, which enjoys some autonomy of management in this area. I look at movements of the Beveridge curve, which draws the classical inverse relation between the job vacancy rate and the unemployment rate, before, during, and after the 2020-2021 pandemic. Since immigration not only expands the supply of labour, but also adds to the demand for labour in the overall economy, its net effect on job vacancies in the aggregate is a priori uncertain. To clarify matters, I present a statistical analysis of pre- and post-pandemic data in the six Canadian regions. Results suggest that the common-sense belief that more immigration contributes to reducing economy-wide labour scarcity is wrong and constitutes a dangerous fallacy of composition. – – La présente étude analyse l'effet de la politique d'immigration expansive du Canada amorcée en 2016 sur la pénurie de main-d'œuvre dans six régions du pays, et tout particulièrement au Québec, qui dispose d'une certaine autonomie de gestion en la matière. J'examine l'évolution de la courbe de Beveridge, c'est-à-dire de la relation classique inverse observée entre le taux de postes vacants et le taux de chômage, avant, pendant et après la pandémie de 2020-2021. Comme l'immigration fait augmenter non seulement l'offre de main-d'œuvre, mais aussi la demande de main-d'œuvre, son effet net sur le taux de postes vacants dans l'ensemble de l'économie est a priori incertain. Pour y voir clair, je présente une analyse statistique des données d'avant et d'après la pandémie dans les six régions du Canada. Elle tend à démontrer que l'hypothèse du « gros bon sens », voulant que plus d'immigration permet d'atténuer une pénurie de main-d'œuvre qui est généralisée dans l'économie, est fausse et constitue un dangereux sophisme de composition.
Keywords: J11; J21; J23; 330; immigration; labour shortages; job vacancies; unemployment; Beveridge curve